THE CORRELATION BETWEEN VOCABULARY AND SPEAKING SKILL - Afna, Mauloeddin (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2018)
The study investigated about the correlation between mastery the vocabulary and fluency in speaking. Vocabulary is the words and exposes in articulation. Therefore, it is related to the utterances delivery fluently. The study applied qualitative method by using a case study. The researcher administrated observation and documentation as instrument of collecting the data. The instruments were carried out to describe the correlation between vocabulary mastery and speaking fluency. The researcher took 11 students as the samples of the study by purposive sampling technique. In addition, the correlation data in speaking tests were analyzed by using speaking assessment measurement systems. There were five times of observation sections. Then, the researcher also documented the final round of speaking test in class. The criteria of speaking assessment measure were; task achievement, fluency, language in use (i.e. vocabulary, pronunciation, and intonation), and duration. The result of the study showed that there are 3 students had score 41-60 (C in numeral core), 2 students had 61-80 (B in numeral score), and 81-100 (A in numeral score). In Conclusion, the result indicated that there is positive correlation between vocabulary and speaking skill. Vocabulary affected the students who fluent in speaking, and influenced vocabulary acquisition.